2022
DOI: 10.1186/s12871-022-01851-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effect of melatonin, dexmedetomidine, and gabapentin on reduction of postoperative pain and anxiety following laminectomy: a randomized clinical trial

Abstract: Background This study aimed to compare the effects of melatonin, dexmedetomidine, and gabapentin on postoperative pain and anxiety following laminectomy. Methods In this randomized clinical trial, 99 patients aged 40–60 years old with American Society of Anesthesiologists physical status I-II undergoing laminectomy were divided into three groups receiving 600mg gabapentin (group G), 10mg melatonin (group M), or starch tablets (group D). The Hospita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 43 publications
1
5
0
Order By: Relevance
“…Additionally, this dose of sublingual melatonin proved effective in enhancing analgesia and reducing the incidence of spinal-related issues in patients undergoing cesarean section under spinal anesthesia. Our findings regarding the analgesic effect of melatonin align with earlier studies, further supporting the efficacy of melatonin as a premedication agent [3,9,[11][12][13]. The results of studies by Khare et al [14] and Lotfy and Ayaad [15] align with that of the current study.…”
Section: Discussionsupporting
confidence: 91%
“…Additionally, this dose of sublingual melatonin proved effective in enhancing analgesia and reducing the incidence of spinal-related issues in patients undergoing cesarean section under spinal anesthesia. Our findings regarding the analgesic effect of melatonin align with earlier studies, further supporting the efficacy of melatonin as a premedication agent [3,9,[11][12][13]. The results of studies by Khare et al [14] and Lotfy and Ayaad [15] align with that of the current study.…”
Section: Discussionsupporting
confidence: 91%
“…Recently, several neuroprotective agents have been identified. Melatonin has shown efficacy as a postoperative anti-anxiety medication, while dexmedetomidine has demonstrated usefulness in alleviating postoperative pain [17]. Metformin exerts neuroprotective effects in neurodegenerative conditions associated with diabetes mellitus by inhibiting inflammation [18].…”
Section: Discussionmentioning
confidence: 99%
“…Several animal [143][144][145][146][147][148][149][150][151][152] and human [153][154][155][156][157][158][159][160][161] studies have shown that melatonin administration exerts an anxiolytic effect. In experimental studies, various paradigms are used to test the anxiety-related behavior of animals.…”
Section: Anxiolytic Effect Of Melatoninmentioning
confidence: 99%